Product Replacement Policy in a Production Inventory Model with Replacement Period-, Stock-, and Price-Dependent Demand - Subhajit Das; Amalesh Kumar Manna; Emad E. Mahmoud; Kholod M. Abualnaja; Abdel-Haleem Abdel-Aty; Ali Akbar Shaikh (Journal of Mathematics)
In the competitive market situation, several companies confer various types of incentives and facilities during product sell to their customers with certain terms and conditions. For the products such as mobile, TV, water purifiers, marshal products, and many more, its corresponding companies offer replacement facility during the guarantee period to enhance the customers’ demand. In this study, we have formulated a production inventory model with considering product’s replacement facility of the failure product within guarantee periods to their customers. This work also leads two vital assumptions: (i) customers’ demand is depending on the replacement period, stock level, and selling price of the product and (ii) the rate of replacement loss of manufacturer’s capital is dependent on the replacement period, and it is a nonlinear function. Since the corresponding optimization problem is highly nonlinear, we have solved it by MATHEMATICA software. The concavity of the centre of interval-valued average profit of the proposed model is shown graphically. In order to justify the validity of the proposed model, a numerical example is considered and solved. Finally, the sensitivity analyses are carried out with respect to the different model parameters.